A novel biscoumarin compound ameliorates cerebral ischemia reperfusion-induced mitochondrial oxidative injury via Nrf2/Keap1/ARE signaling. (1st May 2020) - Wang, Jun; Zhang, Wentong; Lv, Chao; Wang, Yangang; Ma, Bo; Zhang, Haomeng; Fan, Zhaoyang; Li, Mingkai; Li, Xia
Abstract: Some phytochemical-derived synthetic compounds have been shown to improve neurological disorders, especially in ischemic stroke. In this study, we identified a novel biscoumarin compound, known as COM 3, which had substantial antioxidant effects in neurons. Next, we found that COM 3 occupies a critical binding site between the Nrf2 and Keap1 dipolymer, impairing the inhibitory effects of Keap1 on Nrf2, both of which play central roles in increasing endogenous antioxidant activity. We verified that COM 3 could increase the survival of neurons experiencing oxygen and glucose deprivation (OGD) from 51.1% to 77.2% when exposure to 2.5 and 10 μg/mL of COM 3, respectively. In addition, the same concentrations of COM 3 could reduce brain infarct volumes by 33.8%to13.7%, respectively, while also reducing the neurobehavioral score from 3.3 to 1.4 on average in mice with a middle cerebral artery occlusion (MCAO). COM 3 reduced neuronal death from 36.5% to 13.9% and apoptosis from 35.1% to 18.2%. In addition, COM 3 could improve the neuronal mitochondrial energy metabolism after experiencing oxidative stress caused by OGD or MCAO. The present study suggests that COM 3 protects against OGD in neurons and MCAO in mice by interfering with the structure of Keap1 to activate the nuclear transcription of Nrf2, which balances endogenous redox activity and restores mitochondrial function. Hence, COM 3 might be a potential therapeutic agent for ischemic stroke in the clinic. Highlights: Biscoumarin-derivatives have shown neuroprotective abilities in many diseases. A new biscoumarin compound COM 3 protects against ischemic stroke in mice. The neuroprotective effects of COM 3 is related to its antioxidant ability. COM 3 attenuated mitochondrial oxidative stress in ischemic stroke mice. Combination of COM 3 and Keap1 activated endogenous antioxidant activity.